A polo ball in the right atrium, importance of echocardiographic characteristics of intracardiac myxomas: a case report - Mira Hamdan; Boutros Alam; Antoine Kossaify (Journal of Medical Case Reports, 2023)
Abstract Background Myxomas are the most prevalent type of heart tumors, mainly occurring in the left atrium, with approximately 20% of cases found in the right atrium. Timely diagnosis and appropriate management of myxomas are crucial for favorable outcomes and to minimize complications. Case presentation A 77-year-old Asian male with no significant medical history presented with intermittent trepopnea and palpitations. Physical examination revealed regular heart sounds and no other relevant findings. A transthoracic echocardiogram showed a large, round-shaped, smooth-edged mass with diameter of 86 mm, occupying most of the right atrium. Mild tricuspid flow obstruction and mild left ventricular systolic dysfunction were also observed. Cardiac tomography confirmed the size, smooth edges, and showed microcalcifications of the mass, with no invasion of surrounding tissues. Surgical intervention successfully removed the spheroid mass, leading to the alleviation of symptoms. Histopathology confirmed the myxoma nature of the mass. A comprehensive discussion based on relevant medical literature is provided, with emphasis on echocardiographic characteristics of the mass with relation to potential embolic disease. Conclusion This case shows an atypical presentation of an exceptionally large myxoma in the right atrium, resembling the size of a polo ball, in a patient presenting with supraventricular arrhythmia and trepopnea. Early diagnosis and appropriate management played a vital role in achieving a successful outcome for the patient.